Understanding Management in the Management of School Operational AID - Muhamad Fajar Ronansyah; Yanto Yanto; Akhmad Habibi (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to explain the management understanding of School Operational Assistance funds. This research is qualitative research using descriptive methods. Interviews, documentation and observation as data collection. Data analysis used includes data collection, data reduction, data presentation, data verification and final conclusions. The research results show: (1) Program planning is carried out at the beginning of each new school year by the school finance team by involving teachers, committees and parents through meetings and the results of agreements programmed in the RKAS which are guided by 8 SNPs, determining the priority scale and analysis of the amount of funds available, (2) Program implementation begins with coordination and outreach with various parties. The program is carried out in accordance with planning and is guided by the Technical Guidelines for BOS funds approved by the Banda Aceh City Education Office, (3) Supervision is carried out jointly by teachers, committees, school principals, school BOS teams, City BOS and provincial BOS teams as well as each inspectorate. once three months or four times a year.